2016
DOI: 10.1021/acsenergylett.6b00594
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Rich Layered Cathode Materials for Automotive Lithium-Ion Batteries: Achievements and Perspectives

Abstract: Future generations of electric vehicles require driving ranges of at least 300 miles to successfully penetrate the mass consumer market. A significant improvement in the energy density of lithium batteries is mandatory while also maintaining similar or improved rate capability, lifetime, cost, and safety. The vast majority of electric vehicles that will appear on the market in the next 10 years will employ nickel-rich cathode materials, LiNi1–x–y Co x Al y O2 and LiNi1–x–y Co x Mn y O2 (x + y < 0.2), in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
879
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,156 publications
(930 citation statements)
references
References 188 publications
8
879
0
5
Order By: Relevance
“…To date, most review articles have mainly addressed structures, surface chemistry or modification of the cathode materials. [20][21][22][23][24][25][26][27] Although previously published articles well organized the complex properties of cathode materials with respect to structural, chemical, and thermal aspects, a wide range of technical challenges including the stability issue and degradation mechanisms under the industrial electrode fabrication condition have not been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most review articles have mainly addressed structures, surface chemistry or modification of the cathode materials. [20][21][22][23][24][25][26][27] Although previously published articles well organized the complex properties of cathode materials with respect to structural, chemical, and thermal aspects, a wide range of technical challenges including the stability issue and degradation mechanisms under the industrial electrode fabrication condition have not been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Positive electrodes for LIBs to be explored in electric vehicles are mainly based on lithiated transition-metal oxides comprising Ni, Co and Mn (LiNi y Co x Mn 1-y-x O 2 ) and designated as NCM. 1,2 They have attracted much attention as promising materials and therefore many research projects have been dedicated to them in the past 20 years. [3][4][5][6][7][8][9][10][11][12][13] In studies of LiNi 1/3 Co 1/3 Mn 1/3 O 2 (NCM333) cathodes, it was demonstrated [4][5][6] that they provided a capacity of 200 mAh/g in the voltage range of 2.5-4.6 V, or ∼155 mAh/g if the cutoff voltage is limited by 4.3 V. 7 A substantially improved high-voltage performance of NCM333 electrodes (up to 4.6 V) was achieved by introducing tris(2,2,2-trifluoroethyl) borate additive in the electrolyte solution.…”
mentioning
confidence: 99%
“…LiNi 0.8 Co 0.15 Al 0.05 O 2 electrodes demonstrate reversible capacities of ∼200 mAh/g in the range of 3.0-4.2 V; the material has lower cost and is more environmentally friendly comparing to other compositions. 1,2,13 However, NCA electrodes show structural instability, poor cycling behavior at high rates, elevated temperatures and in wide potential ranges, as well as capacity losses of up to 30%. 14 There is a consensus in the literature that the above drawbacks originate from the unstable Ni 4+ ions developed in the charge state (high anodic potential, most Li + extracted from NCA).…”
mentioning
confidence: 99%
“…This is quite cheap and productive technology is used widely for industrial purposes. However, recently there has been a downward trend in the growth of the energy intensity dynamics of the CSC, created by this technology [1][2][3]. Therefore, the urgent task is to find and develop new technologies that will provide the necessary dynamics of energy intensity growth of CSC and UCS.…”
Section: Introductionmentioning
confidence: 99%